Effect of Choline supplementation on rapid weight loss and biochemical variables among female taekwondo and judo athletes - Elsawy, G.; Abdelrahman, O.; Hamza, A. (Journal of Human Kinetics, 2014)
Taekwondo and judo competitions are divided into weight categories. Many athletes reduce their body mass a few days before competition in order to obtain a competitive advantage over lighter opponents. To achieve fast body mass reduction, athletes use a number of nutritional strategies, including choline supplementation. The goal of this study was to identify the effects of choline supplementation on body mass reduction and leptin levels among female taekwondo and judo athletes. Twenty-two female athletes (15 taekwondo and 7 judo athletes) were selected from different weight categories and divided into two groups, according to weight. The players in the experimental group took choline tablets for one week before a competition. The results revealed significant differences between pre- and post-competition measurements of leptin, free plasma choline, urine choline and urine malondialdehyde levels; body mass was also reduced in the post-competition measurements. In conclusion, choline supplementation could rapidly reduce body mass without any side effects on biochemical levels or static strength.